Incremental value of fetal spatiotemporal image correlation echocardiography in the diagnosis of tetralogy of Fallot with disconnected pulmonary arteries with ductus arteriosus supplying the left pulmonary artery - Sonia Karapurkar; Mahesh Kappanayil; Raman Krishna Kumar; Balu Vaidyanathan (Wolters Kluwer Medknow Publications, 2023)
Disconnected branch pulmonary arteries are sparsely reported cases in prenatal diagnosis literature. We report a case of tetralogy of Fallot with disconnected branch pulmonary arteries, the left pulmonary artery (LPA) arising from an indirect ductus arteriosus (DA) from the base of the innominate artery in a right aortic arch, diagnosed by fetal echocardiography with 3D/4D spatiotemporal image correlation (STIC) imaging. Prenatal diagnosis led to early neonatal intervention to maintain blood flow to the LPA by stenting of the DA. Fetal echocardiographic evaluation (Voluson E10 systems, GE Healthcare, Zipf) with acquisition of images and volumes in the right ventricular outflow tract and three-vessel trachea view with rendering of 3D/4D STIC volume datasets to display images in high-definition color format. Prenatal evaluation was initially done at 17-week gestation in a 28-year-old pregnant female which showed tetralogy of Fallot (TOF). Subsequent evaluation at 34 weeks with 3D/4D STIC datasets showed a small main pulmonary artery (MPA) continuing into an adequately sized right pulmonary artery. The LPA was very small (Z-score −2.63), with no visible connection to MPA. Rendering of the 3D/4D STIC datasets revealed disconnected pulmonary arteries with the vertical DA from the base of the innominate artery in a right aortic arch, continuing as the LPA. Findings were confirmed on postnatal high-resolution CT pulmonary angiography and cardiac catheterization with subsequent stenting of the ductus. This report highlights the incremental benefit of advanced 3D/4D STIC rendering in accurate prenatal diagnosis of a rare anomaly of TOF with disconnected pulmonary arteries, leading to early neonatal intervention to preserve the blood supply to the left lung.